Production, Characterization, and Application of Palm Fruit (Arenga pinnata Merr.) Flour in Boba Pearls - Fauzan Azima; Desniarti Desniarti; Muhammad Iqbal; Bunga Silvana Khaira (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2025)
Widely consumed food products can be strategically fortified with dietary fiber to enhance population-level fiber intake. This study examined the physicochemical and functional properties of palm fruit flour to determine its potential as a dietary fiber-enhancing substitute in tapioca-based boba. Initially, palm fruit flour was characterized for its physicochemical and functional properties. Afterwards, it was substituted for 20% of the tapioca in tapioca-based boba pearls and compared to a control (100% tapioca). Analyses of both the raw flour and the boba included its physicochemical and functional properties. Characterization of palm fruit flour showed a high water absorption capacity (8.79 mL/g) and whiteness degree (92.12%). Substituting 20% of the tapioca with palm fruit flour resulted in a product with a high dietary fiber content (20.73%), increased moisture content (68.46 ± 1.25), and a lowered caloric value (2.24 kcal). In conclusion, palm fruit flour is an effective ingredient for fortifying boba nutritionally, though it changes the texture, producing a softer product. Thus, it presents a potentially valuable approach for formulating novel functional foods for healthy consumers, offering a redefined sensory experience. This study is the first to evaluate palm fruit flour as a partial tapioca substitute for fiber-enriched boba production.